THE UTILIZING OF ONLINE LEARNING ON DISCOURSE ANALYSIS AMONG THE STUDENTS OF ENGLISH STUDY PROGRAM DURING COVID-19 PANDEMIC - Merlin Helentina Napitupulu (UICELL, 2021)
This study investigated the students’ ability of using Online Learning on Discourse Analysis majoring English Study Program during Covid 19 Pandemic at Timor University which is located at the border area of Indonesia during Covid-19 pandemic. A total of 35 the fifth semester students of English Study Program participated in this research. The participants who have participated in this research were chosen by applying cluster sampling. The data was collected by discourse analysis test related to experiential metafunction process, and interviewing students to get about the perception on using online learning. Based on the result, the using of Google Classroom could improve the students’ ability on learning Discourse Analysis which is showed by the comparison of pre-test and post test. Some students showed positive perception toward the utilizing of online learning in terms of its usefulness on the learning process. The rest, some of the students prefer offline learning in the classroom because of limited internet access and the students don’t have enough credit to connect to internet access. Thus, the utilizing of online learning has to consider the supporting internet access to make the learning process run well. Keywords: Online learning, Discourse Analysis, experiential metafunction process